2020
DOI: 10.3390/educsci10090216
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning Critical Success Factors during the COVID-19 Pandemic: A Comprehensive Analysis of E-Learning Managerial Perspectives

Abstract: During the COVID-19 pandemic, educational institutions were shut down all over the world, which impacted over 60% of students and caused a massive disruption of the education system. The goal of this paper was to identify the critical success factors for E-learning during COVID-19 using the multi-criteria Analytic Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) techniques to enhance the educational process. Data were generated by interviewing 69 E-learning ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
347
0
29

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(390 citation statements)
references
References 27 publications
14
347
0
29
Order By: Relevance
“…All of the indicated results can be used by teachers conducting classes in distance learning format at a higher level [73]. The information collected through the research shows not only the expectations of students toward distance learning but also their abilities to use IT tools in this process, their enjoyment of the process, and their expectations toward teachers and their engagement.…”
Section: Practical Implicationsmentioning
confidence: 84%
“…All of the indicated results can be used by teachers conducting classes in distance learning format at a higher level [73]. The information collected through the research shows not only the expectations of students toward distance learning but also their abilities to use IT tools in this process, their enjoyment of the process, and their expectations toward teachers and their engagement.…”
Section: Practical Implicationsmentioning
confidence: 84%
“…This was an expected result since the SEU is one of the pioneer public universities in Saudi Arabia and the Middle East Region in e-education, blending learning and innovation in the educational process (S. Saudi Electronic University, 2020). Alqahtani & Rajkhan's study in Saudi Arabia demonstrated that the support of the academic team and educational managers are crucial to reaching a positive educational outcome (Alqahtani & Rajkhan, 2020). Similarly, Bayeck and Lumadi emphasized the importance of teachers' support for the success of eeducational activities (Bayeck, 2016;Lumadi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The official name of this new virus is '2019 novel coronavirus' or . It has disrupted normal life activities for millions of people worldwide, including educational activities (Alqahtani & Rajkhan, 2020;Martins et al, 2020). Lockdowns were announced in several countries and regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perić, Grubišić, and Tijan [43] argued that although the environment for e-learning in many universities exists, it is not sufficiently functional for all learning activities. The success of e-learning during the pandemic era is highly dependent on "technology knowledge management, support from management, increased student awareness of utilizing e-learning systems and demanding high levels of information technology from instructors, students and universities" [44]. Students from lower-income families suffer from the resources of information technology, as they have limited or no access to modern technology [30] and if they do, they face the barrier of excessive internet cost [45].…”
Section: Technologymentioning
confidence: 99%